2009
DOI: 10.1007/s00018-009-9066-x
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate dehydrogenase kinase 4 expression is synergistically induced by AMP-activated protein kinase and fatty acids

Abstract: Organs are flexible as to which substrates they will use to maintain energy homeostasis. Under well-fed conditions, glucose is a preferred substrate for oxidation. During fasting, fatty acid oxidation will become a more important energy source. Glucose oxidation is decreased by fatty acids, a process in which the pyruvate dehydrogenase complex (PDH) and its regulator pyruvate dehydrogenase kinase 4 (PDK4) play important roles. It is currently unknown how energy status influences PDH activity. We show that AMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 44 publications
3
39
1
4
Order By: Relevance
“…PDK4 phosphorylates and inactivates the pyruvate dehydrogenase complex (PDH) during fasting, thereby decreasing glucose oxidation [28,41]. The glucose concentrations that were observed in this study are in line with this because there were no statistically significant differences in glucose levels after 24 h of fasting (online suppl.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…PDK4 phosphorylates and inactivates the pyruvate dehydrogenase complex (PDH) during fasting, thereby decreasing glucose oxidation [28,41]. The glucose concentrations that were observed in this study are in line with this because there were no statistically significant differences in glucose levels after 24 h of fasting (online suppl.…”
Section: Discussionsupporting
confidence: 77%
“…The entry of FFA into mitochondria is a regulated process. Blood glucose levels decrease concomitantly with a decrease in cellular glycolysis and CPT1 is activated permitting the mitochondrial entry of FFA [16,41]. Thus, fatty acids act as the main energy source for cells during fasting [28].…”
Section: Discussionmentioning
confidence: 99%
“…would influence the greater induction observed in the in vivo model than in the C2C12 cells. With the induction of PDK4 (also observed by Houten et al [37] with oleate treatment in hepatoma cells and cardiomyocytes in vitro) the FA can play a direct role affecting the selection of fuel in order to spare glucose.…”
Section: Discussionmentioning
confidence: 99%
“…A low level of AMPK activation within the hypothalamus may be needed for lipid oxidation and torpor to continue, but high levels of AMPK activation will stimulate food intake and prevent torpor. For example, it appears that AMPK may be involved in this switch to fat utilization in heart muscle (Fryer and Carling, 2005;Houten et al, 2009). In the heart of hibernating thirteen-lined ground squirrels (Spermophilus tridecemlineatus), it has been shown that FFAs and insulin shift the fuel utilization within heart tissue by activating pyruvate dehydrogenase kinase isoenzyme 4 and this switch from carbohydrate to lipid metabolism is necessary for successful torpor and may require activated AMPK (Carey et al, 2003).…”
Section: Discussionmentioning
confidence: 99%